Characterization of Vocalizations Emitted in Isolation by California Mouse (Peromyscus californicus) Pups throughout the Postnatal Period - Johnson, Sarah A. (J Comp Psychol, 2017)
Rodent species, such as monogamous and biparental California mice, produce vocalizations as a means of communication. A temporal examination of vocalizations produced by California mice pups in isolation was performed. Pup recordings were performed for 3 minutes at ~10.00 and 14.00 hrs on early postnatal days (PND) 2-4, 7, 21, and 28. Once initial recordings were finished, pups were returned to the home cage with parents and any siblings for five minutes to determine if active biparental responses resulted in an enhanced vocalization response when pups were isolated and retested. We also sought to determine whether potential reduction in vocalizations by older pups might be due to procedure-habituation procedure associated with less anxiety and/or possibly decreased need for parental care. Vocalizations were measured in weanling (30 days of age) “naïve” pups not previously isolated. Results show older pups took significantly longer to vocalize, indicated by increased latency before producing their initial syllable compared to earlier ages. With increasing age, pups demonstrated decreased syllable duration, reduced number and duration of phrases, and decreased number of syllables per phrase. No differences in pup vocalizations were observed before and after being placed back with parents, suggestive biparernal potentiation may not exist in California mice pups. Comparison of the naïve to habituated weanling pups indicates the former group had more total calls but no other differences in vocalization parameters were detected between these two groups. Collectively, the findings suggest that as California mice pups mature and approach weaning they generally vocalize less in isolation.